2000
DOI: 10.1200/jco.2000.18.7.1440
|View full text |Cite
|
Sign up to set email alerts
|

Suramin Therapy for Patients With Symptomatic Hormone-Refractory Prostate Cancer: Results of a Randomized Phase III Trial Comparing Suramin Plus Hydrocortisone to Placebo Plus Hydrocortisone

Abstract: Outpatient treatment with suramin plus HC is well tolerated and provides moderate palliative benefit and delay in disease progression for patients with symptomatic HRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(82 citation statements)
references
References 29 publications
8
73
0
1
Order By: Relevance
“…Verification of this assay system is supported by our data showing VEGF significantly increased angiogenesis in this assay while suramin inhibited angiogenesis by approximately 50%. Suramin is an established anti-angiogenic agent and has been used to treat patients with various cancers (Stein et al, 1989;Danesi et al, 1993;Small et al, 2000). Therefore, the anti-angiogenic potency of these compounds suggests that they may be of improved therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…Verification of this assay system is supported by our data showing VEGF significantly increased angiogenesis in this assay while suramin inhibited angiogenesis by approximately 50%. Suramin is an established anti-angiogenic agent and has been used to treat patients with various cancers (Stein et al, 1989;Danesi et al, 1993;Small et al, 2000). Therefore, the anti-angiogenic potency of these compounds suggests that they may be of improved therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,35,36,39,44,46 This measure, specifically validated on advanced metastatic prostate patients, consists of 30 questions addressing 10 relevant do- 31 the Functional Living Index-Cancer, 45 the Southwest Oncology Group questionnaire (SWOG), 29 and the Functional Assessment of Cancer Therapy. 32 Nevertheless, some trials reported limited information about the nature of the HRQOL measure used while others created ad hoc measures without giving any information about the developmental process. 25,38,48,49 …”
Section: Hrqol Assessment Methodologymentioning
confidence: 99%
“…Ten RCTs were carried out in North America, [25][26][27][28][29][30][31][32][33][34] nine were carried out in Europe, [35][36][37][38][39][40][41][42][43] three enrolled patients from different continents, 44 -46 and three were carried out in Japan. [47][48][49] Bicalutamide, the therapy against which most treatment comparisons were made, was used in seven trials.…”
Section: Demographics and Trial Designsmentioning
confidence: 99%
“…Better assessment of the role of glutocorticoids alone can be obtained from the larger randomised phase III trials that included prednisone or hydrocortisone alone as a control arm. In these studies, the rate of PSA response was in the range 16 -24%, and generally of short duration (Tannock et al, 1996;Kantoff et al, 1999;Small et al, 2000b;Berry et al, 2002). In symptomatic patients, prednisone or hydrocortisone treatment was inferior in improving pain and other symptoms to arms that included mitoxantrone and steroid.…”
Section: Glucocorticoidsmentioning
confidence: 99%